An isotope hydrochemical approach to understand fluoride release into groundwaters of the Datong Basin, Northern China. Issue 4 (6th March 2015) - Su, Chunli; Wang, Yanxin; Xie, Xianjun; Zhu, Yapeng
Abstract : The hydrogeochemical and isotopic investigations of high fluoride (up to 8.26 mg L -1 ) groundwater in the Datong Basin, Northern China were carried out. The elevated δD and δ 18 O, low F/Cl ratios, and the presence of low tritium in the high fluoride groundwater reflected the effects of long water-rock reactions and evapotranspiration. Abstract : The hydrogeochemical and isotopic investigations of high fluoride (up to 8.26 mg L −1 ) groundwater in the Datong Basin, Northern China were carried out in order to evaluate the geochemical controls on fluoride enrichment. The groundwater fluoride concentration tends to increase along with the regional groundwater flow path away from the basin margins, towards the central parts of the basin. Groundwater with high F concentrations has a distinctive major ion chemistry, being generally HCO3 − -rich, Na-rich, Ca-poor, and having weak alkaline pH values (7.2 to 8.2) and Na–HCO3 waters. These data indicate that variations in the groundwater major ion chemistry and possibly pH, which are controlled by water–rock interaction processes in the aquifer, are important in mobilizing F. Positive correlations between fluoride with lithogenic sodium (LNa) and HCO3 − in groundwater show that the high fluoride content and alkaline sodic characteristics of groundwater result from dissolution of fluorine-bearing minerals. The occurrence and behavior of fluorine in groundwater are mainly controlled by fluorite precipitation as a function of Ca 2+ concentration. A positive correlation between fluoride and δ 18 O, low F - /Cl - ratios, and the low tritium level in the fluoride-rich groundwater indicate the effects of long-term water–rock interactions and intensive evapotranspiration.